Transformasi Pendidikan Digital Melalui Gamifikasi Dan Deep Learning: Kajian Literatur Menuju Pembelajaran Berkelanjutan - Dwi Anggraeni Siwi; Nurratri Kurnia Sari; Jullya Dwi Fridyarini (Prosiding Konferensi Ilmiah Dasar, 2026)
Digital education transformation encourages the implementation of innovative learning strategies that are able to improve the quality of learning in primary education. One approach that is growing is the integration of gamification with deep learning to create meaningful, conscious, and fun learning. This article aims to analyze the implementation of gamification in basic education learning and examine its relationship with the deep learning approach as an effort to support continuous learning. The study used the Systematic Literature Review (SLR) method by analyzing eight articles obtained through Google Scholar and Publish or Perish based on the criteria of relevance to the research topic. Data is analyzed through the process of identification, selection, synthesis, and interpretation of research findings. The results of the study show that gamification is implemented through various media and learning models, such as Wordwall, Zep Quiz, Duolingo, Discovery Learning-based multimedia, Problem Based Learning, contextual learning, and e-learning gamification-based. The implementation consistently improves learning motivation, student involvement, concept understanding, learning outcomes, and critical thinking skills. In addition, gamification elements in the form of challenges, points, levels, rewards, and continuous feedback are in line with the principles of deep learning that emphasizes meaningful, reflective, and studentcentered learning. However, the results of the study show that the integration of gamification with deep learning is still limited and has not been comprehensively designed. Therefore, it is necessary to develop a learning model that integrates gamification, deep learning, and the use of artificial intelligence to support continuous learning in primary education